THE MODERN METHODS OF TREATMENT OF ALOPECIA (E Global Congress, 2024)
Pathological process in which there are persistent or temporary, total or partial loss of hair or lack of them. This problem occurs in children and adults, men and women almost equally. Despite the high quantity of researches and existing therapeutic methods of various forms of alopecia, the treatment is still not adequate. To solve this problem, in recent years, attend to meticulously study of structural and morphological characteristics of the skin and scar tissue in the focus, to research of hormonal imbalance and adopt a method of follicular microautotransplantation.